Active processes in the language: the role of code switching in the formation of a language culture in a bilingual society (Eurasian Journal of Philology Science and Education, 2025)
The article examines the phenomenon of linguistic code-switching as an actual linguistic and sociocultural phenomenon in the multilingual space of modern society. The authors define code switching not only as a grammatical or phonetic phenomenon, but also as a communicative strategy reflecting the cultural identity of the speaker. The paper analyzes the mutual influence of languages, their functional roles in the communication process, as well as the types of code switching in the theoretical aspect.In interpreting this phenomenon, the study uses such models as the "matrix language frame" by K. Myers-Scotton, the typology of code switching by P. Muysken, as well as the theories of metaphorical and situational code switching by J. Gamperz and J.-P. Bloom. Special attention is paid to the linguistic behavior of the individual and the dynamics of speech in a multilingual society. The social foundations of the parallel functioning of the Kazakh and Russian languages, as well as the influence of the English language among young people, are considered. The authors attribute the reasons for switching codes to the peculiarities of the language situation, social status, and cultural adaptation processes. This phenomenon is interpreted as a natural process reflecting the communicative adaptation of personality, linguistic flexibility and cultural diversity.In addition, the importance of interaction and mixing of languages in the process of national identity formation and social integration is emphasized. As a result of the study, code switching in the linguistic space is considered as an important mechanism demonstrating the functional interaction of languages and ensuring the implementation of socio-communicative adaptation in modern society.Keywords: code switching, active processes in the language, word etiquette, language culture.